Design Of The "Detectip" Application For Early Detection Of Preeclamsi Risk Factors In Pregnant Women - Endang Astiriyani; Nunung Mulyani; Herni Kurnia (Media Informasi, 2025)
Background: The long form results of the 2020 population census (SP2000) show that the Maternal Mortality Rate (MMR) in Indonesia was 189, while the MMR in West Java Province in 2015 was 823 per 100,000 live births. Preeclampsia is the second cause of maternal death after bleeding, around 24% of maternal deaths are caused by preeclampsia. Obstetric complications that often occur in cases of preeclampsia are stunted fetal growth/IUGR, fetal death in the womb, premature labor, HELLP syndrome (Hemolysis Elevated Liver Enzyme Low Platelet), and eclampsia. Objective: Until now there has been no application related to screening for preeclampsia risk factors, therefore this research aims to design an application to make it easier for health workers to identify risk factors for preeclampsia in pregnant women. Method & Results: The research method used is the Research & Development (R & D) method. The results of the material expert assessment received a score of 82, with a very feasible category and recommended for trial but must first be improved according to suggestions. Meanwhile, the results of the assessment from media experts obtained a score of 95. The conclusion was that this application was very adequate, meaning that this application was very suitable for use in clinical practice. Meets almost all assessment criteria very well. Conclusion: the Android-based application "Detektip" shows that the design of this application is very feasible and can be used.